Taking It Personally: When Energy Policy Becomes a Spite Taking - Warren, Gina; Harralson, Anneka (Columbia Journal of Environmental Law, 2026)
In January 2025, the White House issued a presidential memorandum directing federal agencies to immediately suspend all offshore wind development, including projects operating under existing leases and permits, pending a review of “national energy priorities.” The memorandum instructed the Department of the Interior and related agencies to halt regulatory approvals and freeze federal funding. A subsequent executive order expanded the moratorium by revoking renewable energy subsidies and prohibiting the issuance of new offshore wind permits. Acting pursuant to these directives, the Bureau of Ocean Energy Management (“BOEM”) issued Stop Work Orders to multiple offshore wind projects, including Revolution Wind, LLC, halting billions of dollars in ongoing development and effectively stranding investments made in reliance on vested property rights. This Article introduces the concept of Fifth Amendment “spite takings” to expose a doctrinal vulnerability in takings jurisprudence that threatens the stability of large-scale infrastructure investment and warrants closer attention to governmental motive within the public purpose inquiry. When the government exercises its power not to advance a legitimate public purpose, as required by the Fifth Amendment, but instead to target a disfavored owner or industry out of animus or retaliation, the resulting taking becomes what this Article terms a “spite taking.” This Article first provides background on takings doctrine and the nature of property interests in energy development. It then applies the Penn Central factors to BOEM’s Revolution Wind Stop Work Order, framing the agency action as giving rise to inverse condemnation. The shortcomings of a purely regulatory takings analysis motivate the Article’s central argument: that the presidential directives operate as a functional condemnation subject to the Fifth Amendment’s public purpose requirement. This Article therefore recommends a spite takings balancing test to identify when impermissible motive drives presidential action. Drawing on equal protection and administrative law where courts already assess official statements, procedural irregularities, and patterns of disruption to uncover pretext, this Article argues that similar evidentiary tools should inform takings analysis where animus is alleged.